Serological Cross Reaction among Sonle Causative Agents of WomenAbortions (Toxoplasma gondii & Cytomegalo Virus & Rubella Virus),rvith the Incidence of Hepatitis Virus (B &C) - Gargies Salman, Yahya (Tikrit Journal of Pharmaceutical Sciences, 2023)
Primary maternal infection with infectious agents of abortions in women is frequently associated with transplacental transmission to the fetus. This study was conducted to test the utility ELISA assay to detect recent infection with Toxoplasma (TOXO), Rubella virus (RV), Cytomegalovirus (CMV), the incidence of viral hepatitis B (HBS) & C (HCV) in addition the determination of cross reactivity among serological tests. Three hundred forty three women with high risk of pregnancy (who had previous recurrent abortion & congenital abnormalities) & 60 normal pregnancies (control) were tested for the presence of the tests that described in above. The all rate of infectious agents was 22.15 % that divided into 8.88%, 8.02% & 4.84 % for RV, CMV, & Toxo antibodies respectively. Igm Ab of RV(31.5%) was higher than CMV( 17.6%) & Toxo( 3.39% ) P<0.05.While IgG Ab shows the reveres as 17% for Toxo, followed by 6.75% & 7.89 % for RV& CMV respectively P<0.05. Relationship between distribution of Toxo Ab concerning age was not significant P>0.05. incidence of HCV shows equality rates 2.63% within sero-positive Toxo,RV&CMYV, while HBS shows high occurrence in sero-positive for RV ( 5.26%) than in sero- positive for Toxo & CMV(1.31% )P<0.05. Relationship between frequency of abortions & stillbirthsé& infectious agents was significant P<0.05. In addition .relationship between women occupations & frequency of scro-positive reveals significance P<0.05 especially in sera of homemakers (housewives) than other women occupations. Control groups were negative for viral hepatitis &Toxo, except few cases>0.05.